Role of immunological alterations in oral submucous fibrosis - Sarada Malempati; Vamshi Krishna Guttikonda; Thejasri Vishnubhatla; Mahesh Neerupakam; Sridevi Koduri; Krishnaveni Buduru (Wolters Kluwer Medknow Publications, 2019)
Background: Oral Submucous fibrosis (OSMF) is a premalignant condition affecting the oral mucosa. It is observed to have a multifactorial etiology including genetic predisposition and autoimmune origin. This study aimed to study the etiological role of immunological factors in OSMF. Settings and Design: It was a prospective study carried out in the Department of Oral Medicine and Radiology at Lenora Institute of Dental Sciences, Rajahmundry. Aims and Objective: To estimate and compare the serum IgG and IgA between the OSMF subjects and controls. To assess the statistical significance of the difference in the levels of albumin, globulin, total protein, IgG and IgA between study group and control group if any. Materials and Methods: It was an observational study in which the serum albumin, serum globulin, total protein, IgG and IgA were evaluated in a total of 60 patients who gave consent to participate in the study. Results and Discussion: Increase of IgG was observed in 9 (30%) subjects of the OSMF group and in 4 (13.2%) of the control group. IgA level was increased in 2 (6.6%) subjects of OSMF group and in 5 (16.6%) subjects of the control group. However, this difference was not statistically significant. Conclusion: The findings from the study indicated an alteration in the immunoglobulin level in patients with OSMF. However, the association was not significant. Therefore, further and larger studies are advocated to verify the immunological association with OSMF. One important observation made in the study was a positive association between the duration of exposure and stage of OSMF. This implies that interventions which modify the arecanut chewing habits can bring about a reduction in OSMF and in turn oral cancer.